Strengthening Student Network Competence through the MikroTik Academy Program: Evaluation of the CIRO Model - Husnita, Liza; Ambiyar, Ambiyar; Fauzan, Ahmad; Yasmi, Fifi; Edriati, Sofia (Edujavare Publishing, 2026)
The rapid development of Industry 4.0 and Society 5.0 requires higher education institutions to produce graduates with strong digital competencies supported by internationally recognized professional certifications. One strategic effort to address this demand is the implementation of the MikroTik Academy program, which provides students with the MikroTik Certified Network Associate (MTCNA) certification. This study aims to evaluate the effectiveness of the MikroTik Academy program in strengthening students’ network competence using the CIRO (Context, Input, Reaction, and Outcome) evaluation model. A mixed descriptive approach was employed, involving questionnaires, interviews, observations, and documentation. Data were analyzed using qualitative techniques and descriptive quantitative statistics. The results indicate that the program is highly relevant to student needs and industry demands (context), supported by qualified instructors, standardized training materials, and adequate facilities (input). Participants showed positive responses in terms of learning comfort, clarity of instruction, and increased self-confidence (reaction). In terms of outcomes, the program achieved a very high certification pass rate (96–100%), improved students’ professional readiness, and contributed significantly to institutional key performance indicators related to graduate employability and off-campus learning experiences. Overall, the findings demonstrate that the MTCNA certification program is effective, sustainable, and strategically valuable for enhancing graduate competitiveness and institutional quality.